2019
DOI: 10.1002/mrd.23239
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and hyperandrogenism during pregnancy: Role in programming of cardiovascular disease and infertility

Abstract: Maternal nutritional status programs the development of several systems in female offspring, with effects that depend on the severity, duration, and window of development when the nutritional perturbation is imposed. On the basis of the developmental origins of health and disease concept, we hypothesize that gestational low caloric intake may induce maternal subclinical hyperandrogenism during early pregnancy and compromise cardiovascular health and fertility in the female offspring. To examine this possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…This accounts for approximately 24%-41% of the recommended daily caloric intake for sedentary men and women (See Table 7 for comparison) and can have a severe impact on physical wellbeing. This is particularly concerning given the associated risks for malnutrition, metabolic disturbances, and issues related to fertility [72][73][74][75]. Malnutrition and its subsequent impact on health is particularly concerning given the findings regarding increased consumption of sugar and fat as well as decreased consumption of fruits and vegetables with higher levels of anxiety and depression.…”
Section: Clinical Impactmentioning
confidence: 99%
“…This accounts for approximately 24%-41% of the recommended daily caloric intake for sedentary men and women (See Table 7 for comparison) and can have a severe impact on physical wellbeing. This is particularly concerning given the associated risks for malnutrition, metabolic disturbances, and issues related to fertility [72][73][74][75]. Malnutrition and its subsequent impact on health is particularly concerning given the findings regarding increased consumption of sugar and fat as well as decreased consumption of fruits and vegetables with higher levels of anxiety and depression.…”
Section: Clinical Impactmentioning
confidence: 99%
“…One impressive observation to emerge in the last decade is the finding that early insults to the mother can negatively impact the oocyte and lead to transgenerational effects. Studies in cattle revealed that even mild nutrient restriction during a narrow periconceptional window of time can lead to reduced ovarian reserve, aorta malformation, and hypertension in female progeny (Mossa, Latham, Ireland, & Veiga‐Lopez, 2019), demonstrating the high potential of maternal factors in impacting progeny health. Maternal exposure to low levels of environmental toxins (Hunt et al, 2003; Hunt, Susiarjo, Rubio, & Hassold, 2009; Lawson et al, 2011; Muhlhauser et al, 2009; Susiarjo, Hassold, Freeman, & Hunt, 2007), maternal obesity (Boudoures et al, 2017; Grindler & Moley, 2013), and potential effects of ovarian stimulation and oocyte/embryo in vitro culture and manipulations likewise can disrupt the fragile biology of the oocyte, impacting progeny health.…”
Section: Perspectivesmentioning
confidence: 99%
“…Male offspring from dams gestationally stressed by diet-induced obesity in mice (Fernandez-Twinn et al 2014) and caloric-restricted rats (Berends et al 2013) manifest insulin resistance and impaired adipose insulin signaling characterized by reduced levels of Ir2, Irs1, phosphatidylinositol-3-kinases (Pi3k), and Akt. Associated increases in maternal androgen levels in these models (Table 2) (Maliqueo et al 2017, Mossa et al 2019 suggest that programming of insulin resistance in adipose tissue may be androgen dependent.…”
Section: Adiposementioning
confidence: 97%
“…Maternal under-and over-nutrition have both been linked with the programming of obesity, T2DM, and insulin resistance (Duque-Guimaraes & Ozanne 2013, Vaiserman 2017). In addition to direct effects of the altered nutritional state, these conditions also alter the maternal androgenic milieu (Mossa et al 2019, Pasquali & Oriolo 2019. For example, maternal obesity is associated with increased androgen levels (Whyte et al 2007, Arnon et al 2016, Maliqueo et al 2017, Pasquali & Oriolo 2019, suggesting a potential role for androgens in the programming of offspring phenotypes in such nutritional models.…”
Section: Androgen Programming Of Insulin Resistancementioning
confidence: 99%